2018
DOI: 10.1037/neu0000438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and level of education on neurocognitive impairment in HIV positive Zambian adults.

Abstract: The present study raises the need to investigate factors that could be implicated in the poor neurocognitive performance among the younger, less educated HIV+ individuals in Zambia. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 62 publications
(118 reference statements)
2
12
1
1
Order By: Relevance
“…NCI in older age could be due to the normal process of aging and more attention is needed for this older population. The association of NCI with education in this setting remained statistically significant after adjustment and this is in line with a recent study in sub-Saharan Africa [45]. Attention and memory were the most impaired domains.…”
Section: Discussionsupporting
confidence: 91%
“…NCI in older age could be due to the normal process of aging and more attention is needed for this older population. The association of NCI with education in this setting remained statistically significant after adjustment and this is in line with a recent study in sub-Saharan Africa [45]. Attention and memory were the most impaired domains.…”
Section: Discussionsupporting
confidence: 91%
“…In the symptomatic group, since hemophilic arthropathy and presence of a history of cerebrovascular disorder were identified as risk factors for neurocognitive dysfunction, lifestyle review and regular administration of blood products are also important, and medical staff/supporters are required to manage these patients. In contrast, educational level (university or higher) was an associated protective factor in the NDHH group in this study, and it has been reported that higher education has a protective effect against neurocognitive impairments even for HIV-infected patients [30]. In the future, nurturing professionals who can provide support for these associated factors as rapidly as possible and prepare an appropriate medical environment for neurocognitive dysfunction are required.…”
Section: Discussionmentioning
confidence: 52%
“…A study by Kathy et al in 2010 found that education level significantly affected cognitive functions in HIV patients (Lawler et al 2010). A study by Kabuba et al (2018) found that higher education was protective against the occurrence of HIV-associated neurocognitive disorder (HAND).…”
Section: Resultsmentioning
confidence: 99%